Soil Microbial Assemblages Are Linked to Plant Community Composition and Contribute to Ecosystem Services on Urban Green Roofs - Hoch, Jessica M. K.; Rhodes, Matthew E.; Shek, Kaye L.; Dinwiddie, Devin; Hiebert, Terra C.; Gill, Aman S.; Salazar Estrada, Andrés E.; Griffin, Kevin L.; Palmer, Matthew I.; McGuire, Krista L. (Frontiers in Ecology and Evolution, 2019)
Green roofs are a way for cities to mitigate environmental stressors, such as heatwaves and droughts. However, these environmental stressors can adversely affect green roof vegetation, causing challenges for plant growth and survival and subsequently reducing the ability of green roof systems to deliver critical ecosystem services such as heat mitigation and nutrient cycling. Plant-associated microbes may facilitate the resilience and tolerance of green roof vegetation to climate-associated stress. However, despite their crucial role in plant growth and survival in natural ecosystems, there has been little research on plant-associated microbes in green roof systems. Plant choice on green roofs may also determine which microbes established in green roof growing media, and particular plant-microbial combinations may be more resilient to environmental stress. This project sought to characterize soil microbial community composition on green roofs across New York City with different plant palettes and assess how different combinations of green roof plant species and root-associated microbial assemblages responded to isolated and simultaneous heat and drought treatments. We surveyed green roofs planted with either Sedum species or with a mixed-vegetation palette (i.e. wildflowers, grasses, and succulents). We found that mixed-vegetation and Sedum green roofs had distinct soil bacterial and fungal communities (p<0.0001) with a higher relative abundance of mycorrhizal fungi on mixed-vegetation roofs, and higher pathogen loads on Sedum roofs. Concurrently, we conducted a greenhouse experiment in which plants were grown from seed with live inocula collected from the two different types of vegetation on the green roofs we surveyed. We observed that plant species, soil inoculum, and abiotic stress treatment was correlated with shifts in soil fungal communities. This study demonstrated that soil microbial assemblages on green roofs are linked to the roof vegetation, and that they may facilitate green roof plants’ tolerance and resilience to environmental stressors.